The Society is Expecting You - Raguram, S. (My University, 2019)
As a Chief Editor of the ‘Namathu Eezhanadu’, a registered Tamil daily from Jaffna, there are more than three hundred editorials written by the author and selected 108 of them published from 01.10.2002 to 10.07.2003 have been compiled in this volume. The editorials to a greater extent examine, discuss and explore various issues in social, economic, cultural and political spheres identified during both war and peace times. The title of the book ‘The society is expecting you’ is the reflection of one of the editorials written on the responsibilities of the graduates who pass out from the universities. A large variety of pivotal issues such as issues on rehabilitation, resettlement, political prisoners, finding a permanent political solution, environment protection, anti-peace activities, the need of the North-South relationship, issues related to local sports activities, impacts of geopolitics, lack of employment opportunities for university graduates, improvement of the education system, ethnic co-existence, population of water, rehabilitation of war-affected children, single-headed families, diseases during the rainy period, development of rural libraries, media freedom, the safety of the journalists, impacts of the high-security zones, concentration on weaker sections in humanitarian assistance, abuses on women and children, unbalanced treatment on urban and rural schools, frauds in the public supply of food and necessary goods, voluntary involvement of youths in social services, dependent on freebies are covered in the collection.